An adaptation of a habitat modeling approach to simulate and assess differences between existing habitat suitability criteria (HSC) focusing on brown trout for Greek rivers. - Papadaki, Ch.; Ntonidis, L.; Metzafou, Ag.; Zogaris, S.; Evelpidou, N.; Argyropoulou-Papa, M.; Dimitriou, E. (10th International Congress of the Hellenic Geographical Society, 2014)
The legislative framework in Greece regarding environmental flows is based mostly on hydromorphological criteria with little respect to the biotic elements of the rivers ecosystem. Nevertheless, the European Framework Directive (2000/60) outlines the importance of several groups of aquatic organisms that can be used as indices and provide valuable information about the water needs of the riverine ecosystem. Towards this direction, a habitat modelling approach was applied in this study to simulate and assess the alterations of the Weighted Usable Area (WUA) using existing habitat suitability criteria (HSC) for brown trout (adults and juvenile). Brown trout was selected because it is the most recreationally and economically important species in the study areas. Habitat models are designed for a wide variety of planning applications where habitat ecology is an important consideration in the decision process. Habitat Suitability Index curves used in this study describe the instream suitability of the habitat variables most closely related to stream hydraulics and channel structure (e.g., velocity, depth) for two life stages of the brown trout (adults and juvenile). The Brown Trout data are used provisionally to the complete absence of any local HSI development. For this preliminary application, depth and velocity values were converted into their corresponding habitat suitability index values using a GIS software. Among the HSC examined here, there were those that were cited by Boove (1978) and Raleigh et al (1986) and their development is based on literature sources or professional opinion. The demonstration applied here clearly identifies some of the utility in using HSC to potentially identify critical low-flow periods, where additional flow reductions may adversely affect water use, recreation, and aquatic species. The proposed method should be complemented with the ecological information of native fish species, and tested for transferability in other regions of Greece.